On the Hydrogen Bond Strength and Vibrational Spectroscopy of Liquid Water - Ojha, Deepak; Karhan, Kristof; Kühne, Thomas D. (Scientific Reports, 2018)
In the present work, we introduce two new metrics i.e. hydrogen-bond strength and charge-transfer between the donor/acceptor water molecules as a measure of hydrogen-bond rearrangement dynamics. Further, we also employ a simple model based on energy flux through the donor-acceptor water pairs to quantify the extent of the local hydrogen-bond network reorganization. Most importantly, we report a linear relationship between the OH stretch frequency and the charge and energy transfer through donor-acceptor water pairs. We demonstrate that the vibrational frequency fluctuations, which are used to determine third-order non-linear spectroscopic observables like the short-time slope of three pulse photon echo, can be used as an analog of the fluctuations in the hydrogen-bond strength and charge-transfer. The timescales obtained from our hydrogen-bond strength correlation and charge-transfer correlation decay are in excellent agreement with the computed frequency-time correlation function, as well as with recent vibrational echo experiments.
CRIS-Team Scopus Importer:2023-03-20